Kualitas Penanganan Pengaduan Tindak Kekerasan pada Anak dan Perempuan di Unit Perlindungan Perempuan dan Anak Polda Kalteng - Shanty Bahar Ising; Ayudita Trapsilo Jati (Pencerah Publik, 2017)
This study aims to find out how the quality of complaints of acts of violence against children and women in the Central Kalimantan Regional Police PPA Unit. The method used is the Qualitative method, the research conducted was descriptive research in which the Central Kalimantan Regional Police PPA Unit was the research location. Data collection techniques use observation, interviews, and documentation. Based on the results of the study, the Quality of Handling Complaints on Violence Against Children and Women of the Central Kalimantan Regional Police PPA Unit is still not optimal, because of the five service quality indicators there are two indicators that have not run well, namely Tangibles, and Responsiveness while the three indicators that have gone well are reliability indicator, Assurance, and Empathy.